PLANKTON DYNAMICS AS NATURAL FOOD INDICATORS DURING NILE TILAPIA (Oreochromis niloticus) LARVAL REARING IN AQUAPONIC, BIOFLOC, AND AQUABIOPONIC SYSTEMS - Haeriah, Sri Asnawati; Amir, Sadikin; SETYONO, Bagus Dwi Hari (Journal of Fish Nutrition, 2026)
Plankton communities are important in Nile tilapia larval rearing because they function as natural food, a pathway for nutrient and energy transfer, and an ecological indicator of changes in the rearing medium. This study evaluated plankton abundance, genus composition, and ecological indices during Nile tilapia (Oreochromis niloticus) larval rearing in aquaponic (AP), biofloc (BF), and aquabioponic (AB) systems. A 45-day experiment was conducted using a completely randomized design with three treatments and four replicates. Each experimental unit contained 30 L of water and 30 larvae. Plankton was sampled on days 0, 15, 30, and 45 by filtering 10 L of culture water, concentrating the sample to 50 mL, and observing the concentrated sample using a hemocytometer. Plankton community data were interpreted descriptively, and no statistical significance is claimed for plankton parameters. The three systems developed distinct plankton trajectories. AP showed gradual recovery of plankton abundance and an increase in diversity and evenness by day 45 (H’ = 1.79; E = 0.92). BF produced the highest final abundance, driven by Oscillatoria on day 45 (104.00 ×10³ ind. mL⁻¹; approximately 78% of the community), but showed lower final evenness (E = 0.42) and higher Simpson dominance (C = 0.76). AB showed an early Chlorella peak on day 15 (53.25 ×10³ ind. mL⁻¹) and later shifted toward a more even community by day 45 (H’ = 1.79; E = 0.92). These findings indicate that high plankton abundance does not necessarily represent a balanced natural food community. Based on descriptive plankton community indicators, AP and AB appeared more supportive of balanced plankton communities for tilapia larval rearing, whereas BF required stricter management of organic load, floc volume, pH, and nutrient input to prevent cyanobacterial dominance.